Effects of an improved biomechanical backpack strap design on load transfer to the shoulder soft tissues. (25th July 2018) - Hadid, Amir; Gozes, Gal; Atoon, Avihai; Gefen, Amit; Epstein, Yoram
Abstract: The aim of the present study was to characterize shoulder strap structure and mechanical properties that may alleviate strains and stresses in the soft tissues of the shoulder. Utilizing a finite element model of the shoulder constructed from a single subject, we have quantified skin stresses exerted by backpack straps and the strains at the subclavian artery (SCA). For this end, standard shape straps with stiffness of 0.5, 1.2, and 5 MPa, were compared to the effects of optimized straps; a double-layered (soft outer layer and reinforced internal supporting layer) and newly-designed anatomically-shaped strap. Compared to the standard 0.5 MPa strap, the 5 MPa strap resulted in 4-times lower SCA strains and 2-times lower Trapezius stresses. The double-layered strap resulted in 40% and 50% reduction in SCA strains and skin stresses, respectively, with respect to the softer strap. The newly-designed anatomical strap exerted 4-times lower SCA strains and 50% lower skin stresses compared to the standard strap. This demonstrates a substantial improvement to the load carriage ergonomics when using a composite anatomical strap.